Further studies of dothistromin toxin genes in the fungal forest pathogen Dothistroma septosporum : a thesis presented in partial fulfillment of the requirements for the degree of Master of Science in Biochemistry at Massey University, Palmerston North, New Zealand - Feng, Feng, Zhilun (Massey University, 2007)
The fungal pathogen Dothistroma septosporum is the main causal agent of Dothistroma (red-hand) needle blight, which is a devastating foliar disease of a wide range of pine species. Dothistromin is a difuranoanthraquinone toxin produced by D. septosporum and is considered as a possible virulence factor for the disease. Based on the similarity of chemical structure between dothistromin and aflatoxin (AF) /sterigmatocystin (ST) precursors, nine putative dothistromin biosynthetic genes have been identified, which are homologous to their corresponding genes in the AF/ST gene clusters. However, in contrast to all 25 AF biosynthetic genes tightly clustered in one region (70-Kb) of the genome, the dothistromin gene clusters are located on a 1.3-Mb chromosome and separated into three mini-clusters along with non-dothistromin genes. The dotC gene, located in the mini-cluster 1, is predicted to encode a major facilitator superfamily (MFS) membrane transporter involved in secretion of dothistromin. In this work, by constructing DotC-eGFP fusion protein containing mutants, the subcellular localization of the DotC protein was determined to be mainly targeted to the plasma membrane. The biological function of the dotC gene was characterized by targeted gene disruption. The dotC gene disrupted mutants showed a significant reduction of dothistromin production in both the medium and mycelium. In addition, the exponential growth of dotC null mutants was inhibited when exogenous dothistromin was presented and these mutants also displayed more sensitivity than the wild type strain to exogenous dothistromin. The results indicated that the DotC protein is a membrane associated protein and might have a role in dothistromin production and be involved in secretion of exogenously supplied dothistromin toxin. Two novel dothistromin biosynthetic genes, norA/B and verB (partial sequence), were identified by using degenerate PCR and D. septosporum genomic library screening. The putative NorA/B and VerB are postulated to encode a dehydrogenase and a desaturase, respectively and are similar to AF/ST genes. These findings further confirmed that the dothistromin shares biosynthetic pathway steps with AF/ST.
Keywords: Red band needle blight; Pinus radiata -- Diseases and pests